Improving The Practical Training of Students in The Context of Education Modernization (Texas Journal of Multidisciplinary Studies, 2021)
In the reform of the education system of the Republic of Uzbekistan, the quality of lessons, strengthening the practical training of students, the elimination of all their shortcomings - this is one of the problems of all students, but in all higher education institutions. will not happen. We will consider these shortcomings on the basis of the following criteria.